Kepuasan dan Loyalitas Konsumen pada Lembaga Kursus Bahasa Inggris: Perspektif Experiential Marketing - Evrianti, Hesti; Fadjar, Adfiyani; Anisah, Anisah (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2024)
The research examines the impact of experiential marketing on customer satisfaction and loyalty towards the services provided by MEC Palu, as well as the impact of this satisfaction on consumer loyalty. This research used a descriptive associative approach, and involved 155 MEC Palu members as a sample selected through a stratified random sampling technique. The sample was divided into three different groups. For data analysis, the structural equation modeling (SEM) method was used. The findings show that experiential marketing has a positive and significant influence on both consumer satisfaction and consumer loyalty. Furthermore, there is evidence that shows consumer satisfaction has a positive and significant impact on customer loyalty. This shows that the implementation of experiential marketing strategies is very important to increase customer satisfaction and loyalty at MEC Palu as an effective marketing strategy to maintain and increase customer loyalty through satisfying experiences.